Hubungan Pola Asuh dan Adiksi Internet pada Remaja Kristen di Jabodetabek - Surjanto, Siouw Meiliana Griselda; Helena, Helena (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2024)
Christian teenagers Jabodetabek, like teenagers in general, are vulnerable to internet addiction.The type of parenting style from parents plays an important role in determining the level of internet addiction of adolescents. This study aims to identify differences in the level of internet addiction based on the type of parenting style among Christian adolescents in Greater Jakarta. A total of 291 adolescents participated in this study. This study uses two instruments, namely the Internet Addiction Test (IAT) to measure the level of internet addiction and the Parenting Style Inventory-II (PSI-II) to identify the type of parenting style of parents. The results showed that neglectful parenting was associated with higher rates of internet addiction in adolescents. In contrast, authoritative and permissive parenting, which has a higher level of responsiveness, tends to be associated with lower rates of internet addiction. These findings show the importance of responsive parenting in preventing internet addiction in adolescents.